Green synthesis of reduced graphene oxide for efficient adsorption-photocatalysis studies in methylene blue dye degradation / Valerie Siong Ling Er - Valerie Siong , Ling Er (2020)
Dyes are one of the major components of industrial effluents. Owing to the complex structures of these toxic organic compounds, the removal of dyes from effluents possesses a great challenge in wastewater treatment. In order to tackle this issue, one of the effective methods is to remove dyes via the combination of adsorption and photocatalysis processes. In the present work, reduced graphene oxide (rGO) was fabricated from graphene oxide (GO) by using an environmentally friendly solvothermal approach, whereby ethanol was employed as a non-toxic reductant. In order to investigate the formation of rGO, the reduction of GO was carried out at different reduction temperatures and durations. It was found that GO was successfully reduced at an optimum temperature of 160 °C and an optimum duration of 2 hours. This was due to the partial restoration of sp2 carbon network brought about by the elimination of oxygen functionalities from the surface. With an increase in surface area and a band gap reduction, the rGO-1602 sample was able to achieve the best adsorption (29.26%) and photoactivity (32.68%) towards the removal of methylene blue (MB) dye. The effects of catalyst dosage, initial concentration of dye, light intensity, and pH of solution were also evaluated against the performance of rGO-1602. The results demonstrated that an even higher MB removal by adsorption (87.39%) and photodegradation (98.57%) was successfully achieved when 60 mg of rGO-1602, double 95 W UV lamp, and initial dye solution of 50 ppm at pH = 11 were implemented as the operational conditions. The MB photodegradation efficiency of rGO-1602 was still maintained at more than 90% after five successive cycles, proving its good stability and recycling ability. This study provides a high-performance adsorbent-cum-photocatalyst for the decontamination of dyes from wastewater.